Alexidine Dihydrochloride Attenuates Osteoclast Formation and Bone Resorption and Protects Against LPS‐Induced Osteolysis. (6th January 2016) - Zhu, Xiang; Gao, Junjie; Ng, Pei Y; Qin, An; Steer, James H; Pavlos, Nathan J; Zheng, Ming H; Dong, Yang; Cheng, Tak S
ABSTRACT: Aseptic loosening and periprosthetic infection leading to inflammatory osteolysis is a major complication associated with total joint arthroplasty (TJA). The liberation of bacterial products and/or implant‐derived wear particles activates immune cells that produce pro‐osteoclastogenic cytokines that enhance osteoclast recruitment and activity, leading to bone destruction and osteolysis. Therefore, agents that prevent the inflammatory response and/or attenuate excessive osteoclast (OC) formation and bone resorption offer therapeutic potential by prolonging the life of TJA implants. Alexidine dihydrochloride (AD) is a bisbiguanide compound commonly used as an oral disinfectant and in contact lens solutions. It possesses antimicrobial, anti‐inflammatory and anticancer properties; however, its effects on OC biology are poorly described. Here, we demonstrate that AD inhibits OC formation and bone resorption in vitro and exert prophylatic protection against LPS‐induced osteolysis in vivo. Biochemical analysis demonstrated that AD suppressed receptor activator of NF‐κB ligand (RANKL)‐induced activation of mitogen‐activated protein kinases (ERK, p38, and JNK), leading to the downregulation of NFATc1. Furthermore, AD disrupted F‐actin ring formation and attenuated the ability of mature OC to resorb bone. Collectively, our findings suggest that AD may be a promising prophylactic anti‐osteoclastic/resorptive agent for the treatment of osteolytic diseases caused by excessive OC formation and function. © 2015 American Society for Bone and Mineral Research.